Improving Students’ Reading Skills Through Short Stories At Second Grade Of MTs Al Jamil Bare Eleh - Hafizah, Haerani; Herman; Hendriani, Ria (Universitas Qamarul Huda Badaruddin, 2022)
Reading as one of the language skill has important role in life give birth to the next generation of intelligent, creative, and critical people. However it appears that students still have difficulty in reading, because their pronunciation is still less good and it is sound is still less loud. Students of second grade MTS Al Jamil Bare Eleh face several problems in reading. Based on the results of preliminary studies, it is relevant that students have difficulty reading English text because they still think their pronunciation is not good enough. The purpose of this study was to apply a short story text with the little friendship of the lion and the mouse to improve students’ reading skills. In conducting research, it is expected to improve students’ skills to read English text. To got more accurate data, analytical assessment scores are used to observe students’ reading skills which includes two components of reading, namely: pronunciation, reading aloud. This research used qualitative descriptive analytic and was in fourth meeting, consisted of three stages: (1) planning (2) action execution (3) observation. The result of the research indicate the success of implementing the practice of reading through short stories. An increase in pronunciation scores, and loudness of voice when reading showed that students made progress from pronunciation to reading English text aloud with scores above the average. This means that the research was successful.